'If Today You Hear His Voice …': Repentance, Return, and Reconciliation in the Old Testament. Issue 1 (May 2016) - Guyette, Fred
Repentance, return, and reconciliation are closely related themes in Biblical literature. Here, I trace an arc from Genesis to Nehemiah upon which these themes might be mapped. In Genesis, there are three stories of separated brothers that educate the desire for return and reconciliation. After The Exodus from Egypt, when the wilderness generation has turned away from Yhwh to worship the golden calf, Moses exhorts them: Return to worshiping the God who led us out of slavery into freedom, and obey Him. In The Book of Judges, there is a frustrating cycle in which Israel turns away from God, suffers disaster, and then repents, but soon then they forget about God again, and the cycle is repeated. In Samuel and Hosea, however, repentance begins to escape that cycle and move forward. King Josiah and Jeremiah, too, urge the people of Judah: Return to the ways of The Lord. For Ezra and Nehemiah, it is good for those who have been in exile to return to Jerusalem, but it is much more important that, no matter where God's people are, they learn to examine their consciences through prayer and return to the Lord. With the help of The Psalms, we can discover the meaning of repentance in sacramental and liturgical contexts.